O carnaval de Antares: fantástico e carnavalização literária em Incidente em Antares - Silva, Valeria Cristina da (2014)
In extremely turbulent period corresponding to the decades of 1960-1970 in Brazil, literature has found curious ways. The authors of that period, trying to express the disjunction of Brazilian society, due to the military dictatorship, and aware of the inability to represent the world as a whole, found in the fragmentation of narrative and the use of other narrative resources - as cinema, advertising etc - an esthetic answer for such complex moment. In this scenario, however, stands the figure of Erico Verissimo, who chooses different ways. Respecting his own conception of literature, the author constructed a work averse to these esthetic renovations. Based on the pillars of "realism" Incidente em Antares innovates by introducing the supernatural element, well know by Todorov as "fantastic". Based on some studies related to fantastic literature and the historical moment, in which Incident em Antares was produced, our work has two specific objectives: first of all, to reveal how the fantastic element is articulated in the novel; secondly, to demonstrate how this fantastic element acquires specific characteristics, allowing the emergence of what Mikhail Bakhtin called literary carnivalization. Our main hypothesis is that the literary carnavalization in Incidente em Antares is responsible for its critical feature.